Comparative study on several type of turbulence model available in ANSYS-fluent software for ONERA M6 wing aerodynamic analysis - Md Shah, Mohd Zarif; Basuno, Bambang; Abdullah, Aslam (Penerbit UTHM, 2020)
ONERA M6 wing model is definitive computational fluid dynamic (CFD) validation case for aerodynamic investigations. Therefore, such investigation on aerodynamic characteristics is conducted with commercial CFD software known as ANSYS-Fluent software. The advantages of this software beside offer various flow solvers, this software also provides a various type of Turbulence Models can be implemented. In the present works, an investigation on capabilities of turbulence models available in the ANSYS-Fluent software based on Boussinesq hypothesis had been studied. The investigation had used five type Turbulence Models for evaluating the aerodynamic characteristics of the ONERA M6 wing model. These five turbulent models are: (1) Spalart-Allmaras, (2) k-ε Standard, (3) k-ε Realizable, (4) k-ω Standard and (5) k-ω SST turbulence models. The flow analysis are carried at two different angle of attacks namely at α = 3.060 and α = 6.060. These two angle of attacks correspond with Mach number